Inadequate Timing Limits the Benefit of Antenatal Corticosteroids on Neonatal Outcome: Retrospective Analysis of a High-Risk Cohort of Preterm Infants in a Tertiary Center in Germany - Biedermann, Richard; Schleussner, Ekkehard; Lauten, Angela; Heimann, Yvonne; Lehmann, Thomas; Proquitté, Hans; Weschenfelder, Friederike (Geburtshilfe und Frauenheilkunde, 2022)
Introduction A common problem in the treatment of threatened preterm birth is the timing and the unrestricted use of antenatal corticosteroids (ACS). This study was performed to evaluate the independent effects of the distinct timing of antenatal corticosteroids on neonatal outcome parameters in a cohort of very low (VLBW; 1000 – 1500 g) and extreme low birth weight infants (ELBW; < 1000 g). We hypothesize that a prolonged ACS-to-delivery interval leads to an increase in respiratory complications.Materials and Methods Main data source was the prospectively collected single center data for the German nosocomial infection surveillance system (KISS) between 2015 and 2018. Multivariate regression analysis was performed to determine independent effects of the ACS-to-delivery interval on the need for ventilation, surfactant or the occurrence of bronchopulmonary dysplasia, neonatal sepsis or necrotizing enterocolitis. Subgroup analysis was performed for ELBW and VLBW neonates.Results A total of 239 neonates were included. We demonstrate a significantly increased risk of respiratory distress characterized by the need for ventilation (OR 1.045; CI 1.011 – 1.080) and surfactant administration (OR 1.050, CI 1.018 – 1.083) depending on the ACS-to-delivery interval irrespective of other confounders. Every additional day between ACS and delivery increased the risk for ventilation by 4.5% and for surfactant administration by 5%. Subgroup analysis revealed significant differences of respiratory complications in VLBW infants.Conclusions Our data strongly support the deliberate use and timing of antenatal corticosteroids in pregnancies with threatened preterm birth versus a liberal strategy. When given more than 7 days before birth, each day between application and delivery increases is relevant concerning major effects on the infant. Especially VLBW preterm neonates benefit from optimal timing.
Keywords: antenatal corticosteroids; preterm birth; VLWB; perinatal outcome; respiratory distress syndrome